Aplikasi Pembelian Tiket Bioskop Berbasis Flutter: Integrasi Pilihan Film, Bangku, dan Pembayaran - Dini Mawarni; Richi Andrianto; Dewi Liana; Abdul Azis; Dandi Rusadi; Fajri Rahmansyah; Farhan Fikriyan (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
The proliferation of mobile technology has brought about significant changes in how we interact with various aspects of daily life. In this context, mobile applications have become crucial tools for simplifying diverse processes, including the purchase of movie tickets. Amidst this evolution, the development of mobile applications has gained prominence, and the Flutter platform provides a robust framework for rapidly creating responsive and engaging applications. This study aims to present a Flutter application that allows users to purchase movie tickets with various film choices, seat selections, and payment methods. The application is designed to deliver an interactive and efficient experience for users to access film options, choose desired seats, and complete the payment process through their preferred methods. The development methodology of this study applies a user-centered approach, focusing on intuitive user interface design and implementing features that cater to user needs. Additionally, the research involves integration with payment systems and the relevant business logic associated with ticket purchasing. The outcome of this research is a Flutter movie ticket purchasing application with an appealing and responsive user interface. The application empowers users to select movies they intend to watch, opt for desired seats, and choose the most suitable payment option. Upon successful payment, the application also presents a summary of the ticket purchase data. It is anticipated that this application will contribute positively by simplifying the movie ticket purchasing process, enhancing user experiences, and providing valuable insights into how mobile application development can effectively meet user needs.